SISTEM PAKAR DIAGNOSA PENYAKIT THT (TELINGA, HIDUNG, TENGGOROKAN) MENGGUNAKAN METODE CERTAINTY FACTOR (STUDI KASUS : RSUD H. ABDUL MANAP JAMBI) - simorangkir, lucy (FORTECH (Journal of Information Technology), 2018)
Abstract - ENT (ear, nose and throat) disease is a health problem suffered by many people without knowing the season. Public understanding of ENT diseases is still very poor, it is unfortunate that the actual symptoms can be dealt with early into a more serious illness due to lack of knowledge. In RSUD H. Abdul Manap to consult a doctor must go through several stages from registering at the registration, then to the medical record then to the ENT polyclinic, then the patient must wait for an incoming call to see a doctor to consult or check the patients illness and if the doctor is not available, the patient should wait until the doctor arrives. Things like that can be facilitated by the expert system is a computer program that mimics the knowledge and thought processes of experts in solving a particular problem. In this study made expert system using certainty factor method (factor certainty). Inputs in this system are patient data, symptom data, disease data, knowledge data and polling data. The output of this system in the form of patient data reports, symptoms data, disease data, knowledge data, diagnosis results, and the results of the poll. This system provides an initial diagnosis of ENT disease based on symptoms experienced by the patient. In this system used certainty factor method to provide the level of certainty against ENT disease suffered by the patient. The results showed that this expert system can help the doctors work become easier so as to give the diagnosis of ENT disease.             Keywords: Expert System, ENT Disease, Certainty Factor